A stable bis(benzocyclobutadiene)-annelated tetraazapentacene derivative - Biegger, Philipp; Schaffroth, Manuel; Tverskoy, Olena; Rominger, Frank; Bunz, Uwe H. F. (Chemistry - a European journal, 2016)
Abstract Biphenylene-2,3-dione is a powerful reagent to build up cyclobutadiene-containing azapolyheterocycles. The target structures are formed in high yields through classical condensation of suitable aromatic diamines with the biphenylenedione. To achieve the title compound, the biphenylenedione is coupled with a diaminobenzothiadiazole derivative. Reductive cleavage of the thiadiazole ring and subsequent condensation with the biphenylenedione gives the title compound in which a central tetraazapentacene is flanked by two benzocyclobutadiene units. This compound is stable despite its extended π-system and its optical features are blueshifted in comparison to those of the symmetrical tetraazapentacene.